Wastewater-based epidemiology in Beijing, China: Prevalence of antibiotic use in flu season and association of pharmaceuticals and personal care products with socioeconomic characteristics. (April 2019) - Zhang, Yizhe; Duan, Lei; Wang, Bin; Du, Yulin; Cagnetta, Giovanni; Huang, Jun; Blaney, Lee; Yu, Gang
Abstract: Wastewater-based epidemiology is an emerging field that has mostly been applied to investigate consumption of illicit drugs. In this study, the wastewater-based epidemiology approach was employed to study consumption of pharmaceuticals and personal care products (PPCPs) and measure their prevalence of use in eight densely populated, urban areas of Beijing, China. Ammonium loads were used to estimate the population equivalents of each sewershed. These estimates were applied to calculate population-normalized antibiotic consumption and prevalence of use during flu season, when antibiotics are frequently misused as a medical treatment. Results indicated that 21.9 g d −1 (10 4  people) −1 of ten popular antibiotics were consumed across the eight sewersheds, indicating that 1.98‰ of the 12.5 million population equivalents used these antibiotics during the sampling period. A comparison of these results to calculations made using previously reported data from 2013 suggest that recent Chinese antibiotic control policies have been effective. Uncertainty analyses were conducted to identify the 95% confidence range for antibiotic prevalence of use as 1.44–3.61‰. Human excretion factors were identified as the most sensitive variable. The wastewater-based epidemiology methods were also applied to a wider range of PPCPs, and the results indicated positive relationships between consumption and socioeconomic factors, such as housing price and population density. Overall, this work provides important public health information on antibiotic use and elucidates relationships between PPCP consumption and socioeconomic characteristics. Highlights: Antibiotic loads significantly correlated to NH4 -N equivalent population Novel methods developed to estimate antibiotic consumption and prevalence of use Calculated prevalence of use overlapped with Monte-Carlo uncertainty analysis. Compositional similarities of PPCPs in sewage were identified by cluster analysis. Socioeconomic characteristics were positively associated with PPCP composition.